Patterns of Human-Wildlife Conflict and People’s Perception towards Compensation Program in Nilambur, Southern Western Ghats, India - Rohini, Chelat Kandari; Aravindan, Tharemmal; Das, Karumampoyil Sakthidas Anoop; Vinayan, Pandanchery Arogyam (Conservation Science, 2017)
Aim: The aim of this research was to examine patterns of human-wildlife conflict and assess community perception towards compensation program implemented to ameliorate human-wildlife co-existence. Location: North and South Forest Divisions, Nilambur, South India. Material and Methods: Data were collected from the official archives of applications made by victims or their families at Divisional Forest Office, Nilambur North and South Forest Division, for the period 2010–2013. The data included (a) types of conflict, (b) wildlife species involved in the conflict, (c) dates of application made by applicants, (d) dates of final decision made by concerned authority and (d) relief amount sanctioned. People’s perceptions towards compensation program were gathered using a questionnaire survey (n=179). Key findings: Crop damage was the most common type of conflict, followed by property damage, injury and death by wildlife attack. Crop damage was contributed mainly by elephant (Elephas maximus) (59%) and wild boar (Sus scrofa) (32%). The other wildlife species involved in conflict were bonnet macaque (Macaca radiata) (3.8%), leopard (Panthera pardus) (3.3%), Malabar giant squirrel (Ratufa indica) (0.47%), porcupine (Hystrix indica) (0.29%), Guar (Bos gaurus) (0.95%) and Sambar deer (Cervus unicolor)(0.29 %). On average, people took 13 days to claim compensation, which received decisions in 90 days. The majority of respondents (67%) were not satisfied with the compensation schemes. The main causes of such dissatisfaction were (a) allocation of insufficient money for the compensation (46.6%), (b) prolonged and difficult administrative procedures to make claims (20%), (c) people’s convictions that compensation scheme does not eradicate the conflict (20%) and (d) disbelief on the officials involved in compensation program (6.6%). Conservation implications: Our results suggest that compensation program has not gained acceptance among local community as an effective strategy to mitigate human-wildlife conflict. Although it may reduce hostile attitude towards wildlife, alternative approaches are urgently needed that avoid conflicts.